Awareness and Attitude of Local Communities towards Mangrove Conservation in Tapak Tugurejo, Semarang City - Subekti, Slamet; Risani, Hilda Nurmala (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
This research focuses on the awareness and attitude of local communities towards mangrove conservation in Tapak Tugurejo, Tugu District, Semarang City. Mangrove forests must be preserved so that they grow sustainably to obtain the resources needed to meet the needs of local communities along with the development of the community-based tourism industry. However, successful collaborative management of mangrove forests is challenging because there are no mutual obligations and clear legal commitments regarding community rights in utilizing the mangrove ecosystem. This research aims to (1) determine local community awareness of Tugurejo Semarang mangrove conservation regarding regeneration, restoration, and recreation, and (2) determine local community attitudes towards the Tugurejo Semarang mangrove forest. The relevance of this study is to provide information regarding mangrove conservation which increases the mangrove population in the area thereby providing protection and environmental services for wildlife, ecosystems, and communities in the Tugurejo area of Semarang. The descriptive method is used to identify different variables and presents quantitative research that uses survey methods to collect data from respondents. The findings are expected to show a significant relationship between local community attitudes towards mangrove forests and local community awareness of mangrove conservation in terms of regeneration, restoration, and recreation. The involvement of local communities in preserving the Tugurejo Semarang mangrove forest is very important because both are mutually beneficial. The novelty of this Environmental History perspective assumes the total interaction of local communities with the mangrove forests in their area.
Keywords: awareness and attitudes, local communities, mangrove conservation, Tugurejo Semarang.